Appraisal of umbrella reviews on vaccines - Rosa Katia Bellomo; John P. A. Ioannidis (Communications Medicine)
Abstract Umbrella reviews are systematic reviews of all systematic reviews on a given question and can provide a higher-level view of current available evidence on broad research topics. Given the importance and possible consequences of the insights derived from umbrella reviews, it is fundamental to ensure accurate, comprehensive reporting and methodological rigor in these papers. Here, we present the potential and limitations of these evolving evidence synthesis tools by looking at umbrella reviews published on vaccine research. Vaccines are essential tools in modern medicine for preventing disease and promoting public health. The scientific literature on vaccines grows rapidly as researchers work to improve existing vaccines and develop new ones. More than half a million scientific papers on vaccines have already been published, including several thousands of systematic reviews that aim to appraise and summarize this growing literature. However, as the published systematic reviews are only able to cover a small proportion of the literature it is important to also provide higher-level evidence syntheses. and discuss further improvements that could be made to integrate evidence on vaccines.